Soil–landform Relationship and Pedogenesis of Flood Plain Soils of Mahananda Sub-basin, Bihar - S.K. Reza (Journal of the Indian Society of Soil Science, 2022)
Alluvial flood plain soils are one of the major soil groups in northern Bihar and are highly heterogeneousas a result of the hydromorphic environment in which they are formed. Hence, the present investigationwas carried out to understand the soil-landform relationship in Katihar district of Bihar. Five major landformslike old alluvial plains (1.97%), young alluvial plains (35.64%), meander plains (30.85%), flood plains(25.35%) and, char land and point (4.5%) were identified after visual interpretation of Sentinel-2 data inconjunction with survey of India toposheet and digital elevation model (SRT DEM). The detailed soilsurvey was carried out to understand the variability in the study area and 200 soil profiles were studied indifferent identified landforms. The soils of active alluvial plain (flood plain, char land and point bar)showed wide range of soil morphological properties with lithological discontinuities. Low chroma andvalue in soils of meander plain due to poor drainage conditions and high groundwater table showed gleyingcharacteristics. The soils of young alluvial plain and active alluvial plain showed irregular distribution ofclay content, cation exchange capacity (CEC) and organic carbon (OC). This study indicates that the soillandformrelationship in alluvial floodplains of Mahananda sub-basin partially followed due to massmovement of sediments from Himalayas, periodic flooding and deposition of alluvium during differentfluvial cycles of Mahananda river and its tributaries. This was further confirmed by study on pedogenicindices of different landforms. The study on pedogenic indices in two selected sites (window area) awayfrom the Mahananda river like fine sand/total sand, very fine sand/total sand, sand/silt, silt/clay, index ofweathering and CEC/clay in the study area doesn’t follow the trend in the flood plain as compared to nearlystable land. This may be due to the effect of shifting of river course and their tributaries in the selected twowindow areas across the different landforms. To overcome the above mentioned problems in soil-landformrelationship in the study area, the identified landforms were further sub-divided based on the local factorslike percentage of crop cover and moisture content. In revised landforms soil types present in each landformshowed soil-landform relationship. Thus, the knowledge on soils in relation to landforms vis-à-vis soilproperties and their pedogenesis is useful in understanding their potentials and problems for sustainableland use planning.